The Political Quarterly. (Londen : Political quarterly publishers, 1930)
Since its foundation in 1930, The Political Quarterly has explored and debated the key issues of the day. It is dedicated to political and social reform and has long acted as a conduit between policy-makers, commentators and academics. The Political Quarterly addresses current issues through serious and thought-provoking articles, written in clear jargon-free English."The Political Quarterly plays host to some of the best writing about both topical issues and underlying trends in UK and European politics"Professor Lord Raymond Plant (https://journals.indexcopernicus.com)
Online: https://onlinelibrary.wiley.com/loi/1467923x (enkel registers; login voor fulltext)
Engels
Tijdschriften
Keywords: politieke geschiedenis